Vitis Flower Sex Specification Acts Downstream and Independently of the ABCDE Model Genes - Coito, João L.; Silva, Helena; Ramos, Miguel J. N.; Montez, Miguel; Cunha, Jorge; Amâncio, Sara; Costa, Maria M. R.; Rocheta, Margarida (Frontiers in Plant Science, 2018)
The most discriminating characteristic between the cultivated Vitis vinifera subsp. vinifera and the wild-form Vitis vinifera subsp. sylvestris is their sexual system. Flowers of cultivars are mainly hermaphroditic, whereas wild plants have female and male individuals whose flowers follow a hermaphroditic pattern during early stages of development and later develop non-functional reproductive organs. In angiosperms, the basic developmental system for floral organ identity is explained by the ABCDE model. This model postulates that regulatory gene functions work in a combinatorial way to confer organ identity in each whorl. In wild Vitis nothing is known about the function and expression profile of these genes. Here we show an overall view of the temporal and spatial expression pattern of the ABCDE genes as well as the pattern of VviSUPERMAN that establishes a boundary between the stamen and the carpel whorls, in the male, female and complete flower types. The results show a similar pattern in Vitis species suggesting that the pathway leading to unisexuality acts independently and/or downstream of B- and C- function genes.